The Relation of Actor and Structure In Case of Land Ownership Dualism - Saleh Sjafei (IJOSPOL - International Journal of Social, Policy and Law, 2026)
Several previous studies have shown a tendency for land law structures to experience clashes between customary and non-customary to bring along the consequences of the existence of individual actors in the context of land ownership. Therefore, some actors choose non-customary legal institutions (formal courts) to negotiate even if they cannot determine the legal structure of the land. Thus, it can be argued that there are symptoms of the dualism of land law in Indonesian society, especially in the Aceh community. The discrepancy or tension occurs in the relationship between the spirit of private ownership as a representation of the needs of individual actors with the legitimacy structures of customary law and non-customary law as a representation of communal spirit (structure). Empirical data shows the higher support for stress in regulating private ownership in local communities. The structural system of customary law that recognizes private ownership without formal evidence tends to clash with the national legal structural system based on the land administration system through the National Land Agency (BPN). Customary justice mechanisms that offer communal-religious peaceful solutions are no longer fulfilled as they should be, and they often lead to the stages of the national justice system. This shows the symptoms of injustice, in which individual actors experience uncertainty in the context of communal private ownership on the one hand, and customary justice mechanisms that are inefficient for them on the other. These problems show the dualism of agency-structure relations, in which individual actors are more determined by, and powerless because of a lack of resources in dealing with legitimacy schemes or structural systems of customary law and non-customary law. The existence of the structural principles of customary and non-customary law has been legitimized under the State Law (Agrarian Basic Law, 1960) in the form of a system of administration of national land law. But in practice, the two schemes (adat and non-adat) create a constraining experience in the form of inefficiencies and injustices for individual actors. So, there is a symptom of disorder in the practice of the dualism of the land law which brings with it a lawsuit for redefinition of the ways of life or the dynamics of the ways of the individual actors. In the next stage, the symptom has implications for the relations of actors and the structure of the land law (agency structure) which is contradictory in the society concerned. These situations and conditions have encouraged researchers to understand and explain why this issue is important to study.